Effects of the Serum Calcium and Magnesium Level in the Development and Complications of Pregnancy Induced Hypertension; A Case-control Study among Sample of Iraqi Pregnant Women, 2022 (Journal of Pharmaceutical Negative Results, 2022)
Background: Preeclampsia is a systemic disease characterized by hypertension, proteinuria and edema, which are thought to be the result of diffuse endothelial activation and dysfunction.Aim: This study aims to provide preliminary data that could influence the prevention and management of PIH.Patients and Methods: A case-control study conducted in Salahadeen General Hospital /Gynecology and Obstetrics department during the period from 1st of January to 30th of June 2022. A convenient sample of 100 singleton pregnant women with a live fetus and gestational age of 20 weeks or more were enrolled (50 pregnant women with preeclampsia or eclampsia and 50 pregnant women in good health as control group. Twenty-four-hour automatic blood pressure monitoring was performed and blood was collected for determination of Serum Calcium and Magnesium by Conventional laboratories procedure and manufactures instructions.Results: There was not a significant difference between the studied cases and the control group in terms of patient age, gestational age at the time of sampling, or parity (P>0.05). On the other hand, there was a significant difference between the studied cases and the control group in terms of systolic and diastolic blood pressure (P <0.05).The study demonstrated that Serum calcium mean was significantly decreased in pregnant women with preeclampsia (8.17 mg/dl) as compared with the control group (9.43 mg/dl) (P. value <0.01). The study demonstrated that Serum Magnesium mean was significantly reduced in pregnant women with Pre-eclampsia (1.73 mEq/L) as compared with the control group (2.15 mEq/L) (P. value <0.01). The study demonstrated that Serum calcium and Magnesium mean were significantly decreased in pregnant women with severe preeclampsia (8.01 mg/dl) as compared with the mild preeclampsia (9.43 mg/dl) (P. value <0.01).Conclusions: The study demonstrated that Serum calcium and magnesium significantly decreased in pregnant women with preeclampsia especially in severe preeclampsia. Nutritional health education should be used as a preventive approach to allow the large sector of the developing countries population to maximize the use of the limited resources in the best way.